A new class of luminescent Cu(i) complexes with tripodal ligands – TADF emitters for the yellow to red color range. Issue 18 (1st December 2014) - Gneuß, Timo; Leitl, Markus J.; Finger, Lars H.; Rau, Nicholas; Yersin, Hartmut; Sundermeyer, Jörg
Abstract : A new class of emissive and neutral Cu(i ) compounds with tripodal ligands is presented. The complexes were characterized chemically, computationally, and photophysically. Abstract : A new class of emissive and neutral Cu(i ) compounds with tripodal ligands is presented. The complexes were characterized chemically, computationally, and photophysically. Under ambient conditions, the powders of the compounds exhibit yellow to red emission with quantum yields ranging from about 5% to 35%. The emission represents a thermally activated delayed fluorescence (TADF) combined with a short-lived phosphorescence which represents a rare situation and is a consequence of high spin–orbit coupling (SOC). In the series of the investigated compounds the non-radiative rates increase with decreasing emission energy according to the energy gap law while the radiative rate is almost constant. Furthermore, a well-fit linear dependence between the experimental emission energies and the transition energies calculated by DFT and TD-DFT methods could be established, thus supporting the applicability of these computational methods also to Cu(i ) complexes.